The postoperative Model for End stage Liver Disease score as a predictor of short-term outcome after transplantation of extended criteria donor livers. Issue 6 (June 2017) - Benko, Tamas; Gallinat, Anja; Minor, Thomas; Saner, Fuat H.; Sotiropoulos, Georgios C.; Paul, Andreas; Hoyer, Dieter P.
Abstract : Background: Recently, the postoperative Model for End stage Liver Disease score (POPMELD) was suggested as a definition of postoperative graft dysfunction and a predictor of outcome after liver transplantation (LT). Aim: The aim of the present study was to validate this concept in the context of extended criteria donor (ECD) organs. Patients and methods: Single-center prospectively collected data (OPAL study/01/11-12/13) of 116 ECD LTs were utilized. For each recipient, the Model for End stage Liver Disease (MELD) score was calculated for 7 postoperative days (PODs). The ability of international normalized ratio, bilirubin, aspartate aminotransferase, Donor Risk Index, a recent definition of early allograft dysfunction, and the POPMELD was compared to predict 90-day graft loss. Predictive abilities were compared by receiver operating characteristic curves, sensitivity and specificity, and positive and negative predictive values. Results: The median Donor Risk Index was 1.8. In all, 60.3% of recipients were men [median age of 54 (23–68) years]. The median POD1–7 peak-aspartate aminotransferase value was 1052 (194–17 577) U/l. The rate of early allograft dysfunction was 22.4%. The 90-day graft survival was 89.7%. Out of possible predictors of the 90-day graft loss MELD on POD5 was the best predictor of outcome (area under the curve=0.84). A MELD score of 16 or more on POD5 predicted the 90-day graft loss with a specificity of 80.8%, a sensitivity of 81.8%, and a positive and negative predictive value of 31 and 97.7%. Conclusion: A MELD score of 16 or more on POD5 is an excellent predictor of outcome in ECD donor LT. Routine evaluation of POPMELD scores might support clinical decision-making and should be reported routinely in clinical trials.